2021
DOI: 10.1002/lary.29386
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis Predicts Surgical Site Infection in Head and Neck Microvascular Surgery‐ A Pilot Study

Abstract: Objective/Hypothesis Early and objective prediction of complications in head and neck reconstructive surgery could decrease morbidity and prolonged hospital stays but unfortunately most complications are not identified until their effect is fully realized. There are limited data regarding the association of platelet levels and post‐operative complications. Post‐operative thrombocytosis (POTCT) is proposed as a possible indicator for complications following free‐flap reconstruction. Study Design Retrospective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…7,21,22 Prior studies found that infected patients may present with thrombocytosis even in the absence of other more obvious signs of infection such as an elevated white blood cell count or fever. 23,24 In agreement with the literature in other patient populations, [8][9][10] our findings suggest that thrombocytosis may be a clinical indicator of postoperative infection risk in hip fracture patients. After excluding all patients with preoperative infections and controlling for patient characteristics and comorbidities including white Thrombocytosis in the critically ill or in the setting of tissue damage after injury has been reported to put patients at increased risk of thromboembolic events.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…7,21,22 Prior studies found that infected patients may present with thrombocytosis even in the absence of other more obvious signs of infection such as an elevated white blood cell count or fever. 23,24 In agreement with the literature in other patient populations, [8][9][10] our findings suggest that thrombocytosis may be a clinical indicator of postoperative infection risk in hip fracture patients. After excluding all patients with preoperative infections and controlling for patient characteristics and comorbidities including white Thrombocytosis in the critically ill or in the setting of tissue damage after injury has been reported to put patients at increased risk of thromboembolic events.…”
Section: Discussionsupporting
confidence: 91%
“…1,2,5 Elevated platelet counts have clinically relevant effects on patient outcomes in cardiac, general, neurologic, oncologic, and vascular surgery. [6][7][8][9][10] Recently, abnormally high platelet counts were associated with major and minor Christian A. Gonzalez, BS…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wound complications included surgical site infection (wound dehiscence or wound pus) and fistula formation. 13 Wound dehiscence was defined as the separation of the closed skin incision edge; wound pus was defined as the presence of redness and purulent secretions at the incision; fistula formation was defined as the formation of a pathological channel between the skin and the deep tissue at the wound. Physicians evaluated patients on the 6th postoperative day, at the time of discharge, and at 1 month after the operation.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Mishra et al showed that severe bacterial infections were characterized by high platelet count levels [ 37 ]. Moreover, Harris et al found that increased levels of circulating thrombocytes could be a marker of surgical site infection in subjects that have undergone head and neck surgery [ 38 ]. Infections are associated with a high inflammatory burden, as HT is.…”
Section: Discussionmentioning
confidence: 99%